IMPROVING SPEAKING SKILL BY USING TIKTOK APPLICATION FOR STUDENT OF JUNIOR HIGH SCHOOL - Syahidiyah, Fitri; Handayani, Sri; Amalyasari, Maya Rizki (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Many students need help with speaking English fluently. These challenges often stem from limited vocabulary, nervousness in public speaking, and a need for more confidence in their language abilities. Educators and language instructors have begun exploring innovative approaches to enhance students' speaking proficiency. One such approach involves harnessing the potential of social media platforms, including TikTok. TikTok is a highly rated app in the Google Play Store, which is 4.6, and this application is highly qualified by merging artificial intelligence and image capture. This study investigated the impact of using TikTok on students' speaking abilities. The experimental group, which incorporated TikTok into their learning, showed significant improvements across various indicators, with mean scores increasing from pre-test to post-test in vocabulary (55.81 to 81.75), fluency (56.66 to 78.71), pronunciation (60.30 to 79.72), and comprehension (60.73 to 81.72). Creating and uploading videos on TikTok motivated students to perform better, driven by the awareness of a wider audience beyond their immediate peers. TikTok's features include limited speaking time, the option to retake and revise videos, and enhanced fluency, vocabulary, and self-confidence. However, the study also identified challenges, including internet connectivity issues, high data consumption, and the constraint of limited speaking duration..